2004
DOI: 10.1530/rep.1.00295
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the incidence of polyspermic penetration into porcine oocytes by pretreatment of fresh spermatozoa with adenosine and a transient co-incubation of the gametes with caffeine

Abstract: To reduce the incidence of polyspermic penetration, the effects of transient exposure of washed fresh spermatozoa to caffeine in a brief co-culture in vitro fertilization (IVF) system were examined. A pretreatment effect of spermatozoa with adenosine was also examined. When 5 mmol caffeine/l was supplemented during periods of co-culture and additional culture periods until 8 h after insemination, a shortened co-incubation period of gametes (30 denuded oocytes in 100 ml modified Medium 199-suspended spermatozoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…oocytes. A comparative study was carried out in order to investigate whether there are differences in effectiveness of the mechanisms that inhibit polyspermic penetration, because it is well known that the incidence of polyspermic fertilization is much lower in bovine IVF (Iwata et al 2008, Wang et al 2007) than in porcine IVF (Hancock 1959, Funahashi & Romar 2004, Hao et al 2006. Furthermore, a standard protocol incorporating cross-linkers in IVF, particularly due to the ability of cross-linkers to induce ZP hardening, may facilitate other problems associated with IVF including resistance to infection by viruses (Bielanski et al 2003), such as the transmission of bovine viral diarrhoea virus in abattoirderived in vitro produced embryos (Perry 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…oocytes. A comparative study was carried out in order to investigate whether there are differences in effectiveness of the mechanisms that inhibit polyspermic penetration, because it is well known that the incidence of polyspermic fertilization is much lower in bovine IVF (Iwata et al 2008, Wang et al 2007) than in porcine IVF (Hancock 1959, Funahashi & Romar 2004, Hao et al 2006. Furthermore, a standard protocol incorporating cross-linkers in IVF, particularly due to the ability of cross-linkers to induce ZP hardening, may facilitate other problems associated with IVF including resistance to infection by viruses (Bielanski et al 2003), such as the transmission of bovine viral diarrhoea virus in abattoirderived in vitro produced embryos (Perry 2007).…”
Section: Discussionmentioning
confidence: 99%
“…After coincubation time, putative zygotes were washed twice with fresh TALPp by gentle aspiration through a glass pipette and allowed to continue in culture at 38.5 8C under 5% CO 2 until fixation (at 22 h post-insemination -hpi -in experiment 3 and at 168 hpi in experiment 4, where blastocyst formation was evaluated). The rationale of this methodology is based on using an optimized IVF system for porcine embryo production (Funahashi & Romar 2004).…”
Section: Pigmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a limited exposure of gametes to caffeine significantly reduced the mean number of sperm cells that penetrated into the oocyte and asynchrony in the morphology of sperm nuclei in polyspermic oocytes (Funahashi and Romar 2004). Other epidemiology studies evaluated the timing and amount of caffeine intake by women and men undergoing IVF and gamete intra-Fallopian transfer (GIFT) on oocyte retrieval, sperm parameters, fertilization, multiple gestations, miscarriage, and live births.…”
Section: Caffeine In Assisted Reproductive Techniquesmentioning
confidence: 99%
“…Recently, the author and a colleague found that a transient co-culture of porcine oocytes with spermatozoa in the presence of caffeine followed by an additional culture in the absence of sperm cells and caffeine effectively decreased the incidence of polyspermic penetration without any reduction in the penetration rate (Funahashi & Romar 2004). Since this new in vitro fertilization (IVF) system can separate the process of sperm capacitation and zona binding from the following process of sperm penetration under different conditions, this system may be useful in analyzing further details of the effects of bME during the IVF period.…”
Section: Introductionmentioning
confidence: 99%